A minimum information standard for reproducing bench-scale bacterial cell growth and productivity. (December 2018) - Hecht, Ariel; Filliben, James; Munro, Sarah; Salit, Marc
Abstract Reproducing, exchanging, comparing, and building on each other's work is foundational to technological advances. Advancing biotechnology calls for reliable reuse of engineered organisms. Reliable reuse of engineered organisms requires reproducible growth and productivity. Here, we identify the experimental factors that have the greatest effect on the growth and productivity of our engineered organisms in order to demonstrate reproducibility for biotechnology. We present a draft of a Minimum Information Standard for Engineered Organism Experiments (MIEO) based on this method. We evaluate the effect of 22 factors onEscherichia coli engineered to produce the small molecule lycopene, and 18 factors onE. coli engineered to produce red fluorescent protein. Container geometry and shaking have the greatest effect on product titer and yield. We reproduce our results under two different conditions of reproducibility: conditions of use (different fractional factorial experiments), and time (48 biological replicates performed on 12 different days over 4 months). Ariel Hecht et al. have developed a minimum information standard for use in biotechnology. They show the most important factors in maintaining reproducibility in handling engineered organisms under different experimental conditions.